Konseling Kelompok untuk Meningkatkan Kepercayaan Diri Siswa - Agus Sangidun; Noer Faqih; Azizah Aziz (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2019)
The study of the provision of group counseling services to increase the confidence of class VIII b students in Al-Ma’arif Wuluhan 2017/2018 Academic Year with 23 respondents as respondents. The data collection method used was Observation and Questionnaire, the data analysis used was descriptive data analysis. Based on the results of the initial observation by giving a questionnaire and obtaining the main data with a percentage of students 'self-confidence in the school by 41%, after being given counseling service actions in the group in the first cycle students' self-confidence increased with a percentage of 56%, after the second cycle students' self-confidence in schools has increased considerably, with a percentage of 74%. The provision of group counseling services shows that students' self-confidence in schools has increased. This research activity has been categorized as successful because it reaches the percentage above the predetermined success indicator, which is equal to 65% of the students' self-confidence in school. Therefore the provision of group counseling services can increase the confidence of class VIII B MTs Al-Ma’arif Wuluhan Academic Year 2017/2018 Keywords: Group Counseling, Student Confidence